Synthesis, Characterization and Biological Activity of Mn(II), Ni(II), Cu(II) and Zn(II) Complexes of Schiff Base Ligand - Shrivastava, Snehika; Kumar, Anil; Pandey, Yogesh; Dikshit, S.N.; Shrivastava, Mukesh; Agarwal, D.K. (Asian Journal of Chemistry, 2010)
The Schiff base has been prepared by refluxing S-benzyl dithiocarbazate with o-chloro benzaldehyde in ethanolic media and form coordination compounds of Mn(II), Ni(II), Cu(II) and Zn(II) metal ions. These complexes were characterized by elemental analysis, molar conductance, infrared, NMR and electronic spectra. Infrared spectral data of the complexes have revealed bidentate complexing nature of the Schiff base through thioketo sulphur and azomethine nitrogen atoms. The possible structures for all the metal complexes are reported here. The antibacterial and antifungal activity of the Schiff base and their complexes have also been screened.